Molecular mechanisms of modern and ancient Paget's disease - Navarro Martínez, Ana (2017)
The project included two interrelated elements relevant to disease mechanisms in modern and ancient Paget’s disease of bone (PDB), a chronic bone disorder characterised by focal regions of increased osteoclast-mediated bone resorption accompanied by increased osteoblast-mediated formation of new, highly disorganised bone. Numerous different mutations (>30) affecting the SQSTM1 gene have been identified in patients with PDB, to date several of which have been studied at the level of protein function. The UBA domain of SQSTM1/p62 is involved in the ubiquitin-binding ability of the protein, important for its roles in the regulation of osteoclast RANK-NF-κβ signalling and cargo recognition for autophagy. Regarding studies of ‘modern’ PDB, we found that a newly identified and uncharacterised PDB-associated UBA domain missense mutation of SQSTM1/p62, F406V, was associated with loss of ubiquitin-binding but normal LC3B-binding function in vitro. We went on to assess the effects of over-expression of different PDB-associated mutants of SQSTM1/p62 (including F406V) on autophagy markers (LC3B-I and LC3B-II) in HEK293T cells under different conditions. Results suggested that the crude transient transfection-based assays may be insensitive to determine any differences in autophagy that may be imparted by PDB-associated mutations of SQSTM1/p62. Regarding studies of ‘ancient’ PDB, we extended an ongoing project in the lab with the aim of unlocking the ‘chemical memory’ of ancient bones from the Norton Priory collection of medieval skeletons and specifically use a combination of molecular approaches to investigate if the individuals were affected by an ancient form of PDB. Our western blotting studies indicated that 1/2 petrous and 1/3 tooth samples tested from skeletons with PDB-like changes were positive for ancient SQSTM1/p62. Previous LC-MS/MS analyses combined with epitope mapping of the mouse antibody supported the notion that the positive samples may contain E396X mutant SQSTM1-p62 protein, known to be associated with familial PDB in modern cases. The results of this study provide, for the first time, a reliable diagnosis of PDB in ancient times, which gives new impetus to further studies in the field of the comparative evolution and the history of bone disease from ancient and to modern times.